Olebolo: Sastra Lisan dan Ritus Petani (Kolaborasi Kearifan Lokal dan Rekayasa Sains dalam Praktik Petani di Tidore) - Yuliana; Bustamin Wahid; Nanik Purwanti; Uswatul Mardliyah (Universitas Muhammadiyah Sorong, 2022)
This article aims at describing two important things in the agricultural tradition in Tidore, namely about olebolo as an oral literary expression of the Tidore farmer entity and farmer rites in agricultural practice in Tidore. This study used a folklore perspective with a phenomenological research type. The author used the Indonesian oral literature expert Endaswuara as a theoretical basis, besides that the author used the economic theory of farmer J. Scott to read, and direct the research in depth. Our findings show that olebolo is an oral literature of farmers singing when they are in the fields and gardens, olebolo is also an encouragement and has mystical and moral content as a true farmer and is able to bring strong solidarity between humans. In addition, the agricultural process in Tidore, especially in Gurabunga, still carries out rituals in the farming process, such as determining the good day during the process of land clearing, planting and harvesting, all of which contain a mystical dimension. Although this ritual is filled with a mystical mechanism, the farmers in Gurabunga also prioritize science, especially the engineering problem of farmers through fertilizers, agricultural bricks can improve the quality and quantity of the harvest. This integration of practice in the world of agriculture shows that the farming community in Gurabunga, cassava with local wisdom but they are so open to the presence of knowledge. Keywords: Oral literature, Farmer’s rite, Tradition-science collaboration